Critical Synthesis of Morality in Islam: A Study of Al-Ghazali's and Ibn Miskawaih's Thoughts - hutomo, arif (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
In the contemporary era, moral crises often separate the social and spiritual dimensions of human ethics, creating a void in a comprehensive understanding of morality. Therefore, this study critically analyzes and synthesizes the thoughts of two of the most influential Muslim thinkers in the field of ethics (akhlaq), Al-Ghazali and Ibn Miskawaih. This research aims to answer how these two thinkers construct the concept of morality within the context of Islamic ethics.This study employs a qualitative analysis with a comparative approach. Primary texts of Al-Ghazali and Ibn Miskawaih are examined to identify similarities and differences in their views on morality. The theoretical framework utilized includes Islamic ethical theory and moral philosophy, allowing for a deeper understanding of the values espoused by both figures. The findings indicate that while Al-Ghazali emphasizes the spiritual aspect and the relationship between humans and God, Ibn Miskawaih focuses more on character development and social ethics. Nevertheless, both contribute significantly to the understanding of morality in Islam. This synthesis of thought is expected to provide new and relevant insights for contemporary studies of Islamic ethics, bridging the dichotomy between the spiritual and social aspects of morality that frequently occurs today. So This study offers an integrative moral framework that is valuable for advancing contemporary Islamic ethical discourse